A Preliminary Study of D-Cycloserine Augmentation of Cognitive-Behavioral Therapy in Pediatric Obsessive-Compulsive Disorder - Storch, Eric A. (2010)
BACKGROUND: Research on the neural circuitry underlying fear extinction has led to the examination of d-cycloserine (DCS), a partial agonist at the NMDA receptor in the amygdala, as a method of enhancing exposure therapy outcome. Preliminary results have supported the use of DCS to augment exposure therapy in adult anxiety disorders; however, no data have been reported in any childhood anxiety disorder. Thus, we sought to preliminarily examine if weight-adjusted DCS doses (25 or 50mg) enhanced the overall efficacy of cognitive-behavioral therapy (CBT) for pediatric obsessive-compulsive disorder (OCD). METHOD: Participants were 30 youth (ages 8–17) with a primary diagnosis of OCD. The study design was a randomized, double-blinded, placebo-controlled augmentation trial examining CBT+DCS versus CBT+Placebo (15 youth per group). All patients received 7 E/RP sessions paired with DCS or placebo taken 1 hour prior to sessions. RESULTS: Although not significantly different, compared to the CBT+Placebo group, youth in the CBT+DCS arm showed small-to-moderate treatment effects (d=.31 to .47 on primary outcomes). No adverse events were recorded. CONCLUSIONS: The present results complement findings in adult OCD and non-OCD anxiety disorders and provide initial support for a more extensive study of DCS augmentation of CBT among youth with OCD.